2014
DOI: 10.1016/j.neuroscience.2014.04.038
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of understanding cerebral white matter injury in the premature infant

Abstract: White matter injury in the premature infant leads to motor and more commonly behavioral and cognitive problems that are a tremendous burden to society. While there has been much progress in understanding unique vulnerabilities of developing oligodendrocytes over the past 30 years, there remain no proven therapies for the premature infant beyond supportive care. The lack of translational progress may be partially explained by the challenge of developing relevant animal models when the etiology remains unclear, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 241 publications
(267 reference statements)
2
44
0
Order By: Relevance
“…In fact, an over functioning OXPHOS is a primary source of ROS [32]. Premyelinating axons are particula r ly sensitive to oxidative stress, recently implicated in OPC death [4]. The oligodendrocyte lineage in the human premature brain is a vulnerable cell population (reviewed in [33]).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, an over functioning OXPHOS is a primary source of ROS [32]. Premyelinating axons are particula r ly sensitive to oxidative stress, recently implicated in OPC death [4]. The oligodendrocyte lineage in the human premature brain is a vulnerable cell population (reviewed in [33]).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…Since the 1960s (Banker and Larroche, 1962) unique VLBW infant white matter lesions have been described, consisting of coagulative necrosis known as periventricular leukomalacia (PVL). Recently, association of PVL with inflammation (O'Shea et al, 2013) and oxidative stress [4] was reported. Studies on titration of supplemental oxygen are suggestive of a primary role of hyperoxia in these lesions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system injury in preterm infants often localizes to the white matter tracts (i.e., connectome) in the brain (105). Hence, imaging techniques that define injury to the connectome is receiving high interest (106,107).…”
Section: Neonatal Nutrition and Modifications Of Gba Functionmentioning
confidence: 99%
“…Focal lesion involve degeneration of axons and glia in the injured area. 4,21 Microscopic injuries are more common than cystic injuries (which tend to be more severe). 1,4 Diffuse PVL is characterized by damage to pre-myelinating oligodendrocytes (pre-OL) leading to hypomyelination, astrocystosis and microgliosis.…”
Section: Pathogenesis Of Brain Injury In Preterm Infantsmentioning
confidence: 99%